Reliability and validity of the modified shuttle test-paeds to measure cardiorespiratory fitness in children - WFM Aertssen; A van de Kamp; LD Jelsma; BCM Smits-Engelsman (BMC, 2024)
Abstract Background The Modified Shuttle Test-Paeds (Paeds), a recently developed 10-meter Shuttle run test for aerobic capacity in children. This study aims to investigate the construct validity (known-group and convergent validity) and test-retest reliability of the recently developed test for cardiorespiratory fitness, the Modified Shuttle Test-Paeds (Paeds). Methods A total of 144 participants (6-12 y) were tested on the Paeds test, and 84 children were tested on the 20-meter Shuttle Run test (20 m-SRT) to assess construct validity. To evaluate test-retest reliability, 46 children were tested twice on the Paeds. Results No sex differences were found, but there was an age effect. A strong correlation was found between Paeds and the 20 m-SRT (rs=0.78, p < 0.001). The test-retest reliability was good (ICC 0.84; 95% CI 0.74-0.91). Conclusion Paeds appears to be a reliable and valid tool for estimating cardiorespiratory fitness in typically developing children aged 6-12 years and has the advantages of being shorter, needing less space, not requiring pacing and being self-motivational. More studies are needed to assess whether children reach an aerobic steady state in three minutes and how much of the results of the Paeds test can be explained by the agility component of the task (turning and grasping or aiming a bean bag). For clinical use, psychometric properties should be studied in various patient groups (e.g., ADHD, DCD, and children with intellectual disabilities).